Perfuração indiscriminada de poços em Iracema/CE: um estudo sobre o paradoxo da atual crise hídrica - Dias, Ana Carla Holanda (Universidade Federal Rural do Semi-Árido, 2017)
In the face of all environmental degradation and current water shortages, groundwater resources are emerging as a new hope for survival. However, the way this resource is exploited does not differ from the unscrupulous way in which surface water is used: indiscriminately. It is important to discuss in what state, in the near future, the water resources will be found, in general, if the exploration continues in this way. Thus, this work provides data and information that seeks to elucidate the problem that concerns society, especially the communities living in the Northeast of the country, which are gradually affected, without the least astonishment about the situation. This study explains the order in which the crisis is established, and the urgent solution of well digging. The area of study adopted was the city of Iracema, in the state of Ceará. As a sample of the region, the situation described in this site happens in several Northeastern municipalities. The paradox between the need to exploit underground water and the awareness of the problems arising from this exploration becomes evident. The drilling of artesian wells appears as an alternative for the supply of regions where the water available on the surface is scarce or nonexistent. Nevertheless, in view of the survey of the number of wells in the study area, it was concluded that the exploitation of groundwater in the municipality of Iracema through artesian tubular wells occurs in a disorderly manner, without estimating the consequences of this practice. Because of this, the level of the water table of the region tends to be lowered, and the area is propitious to the soil subsidence in the future. Thus, it is important that special attention be devoted to the use of these reserves, so as to preserve the most important patrimony of the northeastern backwoods.
Keywords: Poços Artesianos; Artesian Wells; Água Subterrânea; Subterranean Water; Estiagem; Drought; ENGENHARIAS::ENGENHARIA CIVIL